EXPLORING FACTORS THE CHILDREN’S MEANING IN PARENTS’ PERSPECTIVE: FOCUSING ON EDUCATION, FAMILY STATUS, ORIGINAL COUNTRY, RESIDANCE, AND BELIEF SYSTEM - Ghozali Rusyid Affandi; Nur Habibah (Proceedings of The ICECRS, 2016)
There are different perceptions about the meaning of childrenin each person. The different is caused by various factors of the parents. Different definition about the child also has an impact on the treatment of parents towards their children. This research aims to explore the factors in defining children by parents, mainly on demographic factors and beliefs on Islam in Asean area. This study involved 94 participants consisting of citizens of Indonesia and Thailand. The data instrument was open ended questionnaire. Data analysis in this study used descriptive analysis in the form of crosstabulation to explore the definition of a childbased on demographic point of view and belief system (the system of beliefs that is owned by the parent on religion). The results show that there was a universal definition of child from different backgrounds including: education, belief system, original country, status in family, and home, namely a child is the mandate (amanah) from Allah SWT. However, the research also shows the unique and various definition of the children which is seen from each factor.